Implementing AI in Arabic Language Learning: Challenges and Insights from Islamic Higher Education - Rabiatul Adawiyah (STAI Hubbulwathan Duri, 2025)
Artificial Intelligence (AI) is increasingly influencing educational practices, including Arabic language instruction in Islamic higher education. Despite its potential, AI integration encounters technical, pedagogical, and cultural obstacles. This qualitative study employed a case study design at the State Islamic University of Mataram. Data were gathered through in-depth interviews with six Arabic language lecturers actively using AI in their teaching, classroom observations of AI-assisted learning, and document analysis. Thematic analysis was used to identify key patterns and challenges. Findings indicate that lecturers generally view AI positively, recognizing its potential to enhance instructional effectiveness and student understanding while still emphasizing the essential roles of teachers and learners. However, several barriers hinder full integration. These include inadequate technological infrastructure, limited student preparedness, difficulty among lecturers in adapting to digital tools, scarcity of Arabic-specific AI datasets, and technical limitations of AI applications. Although lecturers acknowledge the value of AI in Arabic language education, its practical application is constrained by infrastructural and human resource limitations. Addressing these issues is vital to realize the benefits of AI-enhanced learning environments. This study provides valuable insights into the challenges of AI implementation in Arabic language teaching. It highlights the need for strategic, inclusive approaches by educators, institutions, and developers to ensure effective and sustainable AI integration in Islamic higher education.